Peningkatan Keterampilan Ekonomi Kreatif melalui Pelatihan Fotografi, Desain Grafis, dan Editing Video di Rumah Kreatif Wadas Kelir, Kabupaten Banyumas - M.Lukman Leksono; Robert Hendra Yudianto; Agatha Dinarah Sri Rumestri; Shintia Dwi Alika (Politeknik Piksi Ganesha Indonesia, 2026)
Community service is an implementation of the Tri Dharma of Higher Education aimed at enhancing community capacity and self-reliance. Wadas Kelir Village, Banyumas Regency, has significant potential in culture, arts, and micro, small, and medium enterprises (MSMEs), yet this potential is not optimally supported by adequate digital promotion skills. This program aims to improve photography, graphic design, and video editing skills through training and mentoring activities conducted at Rumah Kreatif Wadas Kelir. The methods applied include a participatory approach, interactive workshops, project-based learning, and continuous mentoring. The results indicate an improvement in participants’ ability to produce visual content for MSME promotion and village branding, as well as the formation of village-based digital creative.